Enhancing digital engagement: The role of cognitive evaluations and affective aspects in airline web application commitment - Kasmo, Arief Bowo Prayoga; Sukardiman, Diah Fistiani; Nugroho, Lucky (Edelweiss Applied Science and Technology, 2025)
The growing digitalization of airline services has increased competition, requiring airlines to enhance user experience on their web applications. However, a significant gap remains in understanding how cognitive evaluations and affective aspects influence behavioral commitment in airline web applications. While previous studies have examined these variables separately, limited research integrates them within a holistic model. This study investigates the impact of cognitive evaluations—perceived ease of use, perceived usefulness, perceived interactivity, perceived information quality, and e-trust—on e-satisfaction and how e-satisfaction mediates the relationship between cognitive evaluations and behavioral commitment. Data were collected from 398 airline web application users in Indonesia and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that all cognitive evaluations, except perceived interactivity, significantly impact e-satisfaction. Moreover, e-satisfaction positively influences behavioral commitment, confirming its mediating role. These findings highlight the need for airlines to improve usability, ensure high-quality information, and build trust to enhance user engagement. The study contributes to the Cognitive-Affective-Behavior (C-A-B) model by integrating Technology Acceptance and Relationship Quality theories. Practically, it offers strategic recommendations for airlines to enhance web application functionality and foster long-term user commitment. The novelty of this research lies in its comprehensive approach to digital consumer behavior within the airline industry.